El club de la dinamita : cómo una bomba en el París de fin de siècle fue el detonante de la era del terrorismo moderno - Merriman, John M., (Colección Hitos., 2020)
Información de la edición en inglés " On a February evening in 1894, a young radical intellectual named Émile Henry drank two beers at an upscale Parisian restaurant, then left behind a bomb as a parting gift. This incident, which rocked the French capital, lies at the heart of The Dynamite Club, a mesmerizing account of Henry and his cohorts and the war they waged against the bourgeoisie - setting off bombs in public places, killing the president of France, and eventually assassinating President McKinley in 1901.